Dua Strategi Misi Mahasiswa Sekolah Teologi di Indonesia Masa Kini - Johana Betris Tumbol (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2021)
The purpose of this research is to find a mission strategy that is relevant to the students of the Theology school in Indonesia today. The methodology used is qualitative research on matters related to the library, by first knowing the practical usefulness of the topic to be researched. The author uses a tool that is mapping the research topic. Writers of literature through the Publish or Perish application and collect information about the missions carried out by Theology school students through interviews, then the author uses the results of the literature and interviews and makes a synthesis of the mission strategies of Theology school students so as to produce new findings in the form of conventional mission strategies for returning home missions. as a short-term mission, and a non-conventional mission strategy, namely a mission on social media as a mission strategy for students of theology seminary in Indonesia. Tujuan dari penelitian ini adalah untuk menemukan strategi misi yang relevan dengan mahasiswa sekolah Teologi di Indonesia masa kini. Metodologi yang dilakukan adalah penelitian kualitatif berupa tinjauan Pustaka, dengan mengidentifikasi terlebih dahulu topik yang akan diteliti mengenai kebermanfaatannya secara praktis. Penulis menggunakan alat bantu yaitu map a reseach topik. Penulis mengumpulkan literatur-literatur melalui aplikasi Publish or Perish dan mengumpulkan informasi mengenai misi yang dilakukan mahasiswa sekolah Teologi melalui wawancara. Kemudian penulis menggunakan hasil tinjauan Pustaka dan wawancara tersebut dan membuat sintesis mengenai strategi misi mahasiswa sekolah Teologi sehingga menghasilkan temuan baru berupa strategi misi konvensional yaitu misi pulang kampung sebagai misi jangka pendek (short-term mission), dan strategi misi non konvensional yaitu misi di media sosial sebagai strategi misi bagi mahasiswa sekolah Teologi di Indonesia.